Co-designing a website with and for youth, so they can better manage their health - Coyne, Imelda (My University, 2023)
Objective: To co-design a website aimed to empower youth to ask questions to encourage productive, meaningful conversations with their health care providers. Methods: The research team recruited adolescent stakeholders (ages 11-17) through flyers distributed at local Young Men's Christian Association (YMCA) locations, clinics, and school nurses. Eleven adolescents who had at least one chronic medical condition were selected as members of the two youth advisory boards. Youth participated in five co-design meetings to give input on website content and refinement over a two-and-a-half-year period. The youth reviewed the website in various stages of development. Results: Youth wanted a website with simple, straightforward language that would be understood by someone between the ages of 11-17 years with a reputable URL. The website content includes ADHD, asthma, vaping/smoking, diabetes, seizures, anxiety, panic disorder, depression, addiction, stimulants, bullying, eating disorders, and sexually transmitted infections. Youth wanted general background content, helpful resources, question prompt lists, and videos encouraging youth involvement in care. Conclusions: A credible co-designed website with information on different health topics that contains question prompt lists and videos for utilization during health care visits has the potential to increase adolescent involvement in their care. Innovation: This website is an innovative intervention aimed at informing and encouraging youth to be more actively involved in their care across a range of healthcare conditions.
PUBLISHED
Keywords: Adolescent; Empowerment; Health; Question-asking; Videos; Website; Youth; Digital Engagement; Adolescent Health; Chronic Illness; Chronic Illness self-management; Digital Health; Health outcomes; Public health